The modern differentiation of language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article analyzes the differentiation of language, due to automatic analysis and synthesis of scientific texts, logical-linguistic models in control systems engineering and the emergence of linguistics. Substantiates the idea how the new sections of linguistics, which emerged as the result of the interaction of different social needs: the desire of mathematicians to use a language material for the explication of new ideas, the creation of artificial intelligence, heuristic modeling of complex and supercomplex systems. The author gives examples of replicable models that are built under the scheme that includes feedback, which performs the function of a correspondence between engineering and reproduction of linguistic object. These models are used in the machine annotation, summarization-translation and machine dialog systems, artificial intelligence. The most typical engineering-linguistic reproducible models can be called the algorithm of automatic recognition of the meaning of the text. Reproductive linguistic modeling today called engineering to linguistics. There are three types of natural languages that are used in practice in pure and in mixed form. In the simulation, special attention is drawn to the epistemological features of the model and ontological similarity to the original models. Natural speech develops on the basis of associative thinking, therefore meaning the contacts have a logical, emotional and aesthetic nature. The author gives the definition of the model in both linguistic and structural sense.
Keywords: linguistic Cybernetics; linguistics; the automatic analysis of lexical units; artificial model; heuristic modeling; linguistic facility; mathematical explication